Internal continuatives and logical metaphors: A development of classifying conjunctive relation - Santosa, Riyadi; Sumarlam; Wiratno, Tri; Priyanto, Agus Dwi; Susanti, Ratna (Universitas Muhammadiyah Sidoarjo, 2021)
This research attempts to develop Martin’s & Rose’s concept of conjunctive relation (CR) analysis, in which the external and internal roles of conjunction do not include the other two types of conjunctive relation markers such as continuative and logical metaphor. Relying on more than twenty international journal articles, the research findings exhibit that certain types of continuative and logical metaphor can not only operate externally to connect events and qualities but they can also function internally to organize evidences and arguments in texts. As a result, not only a new role of internal continuative and logical metaphor can be confirmed, but the findings will also introduce an elaborated development of classifying CR in general. The emergence of the internal role of continuative and logical metaphor leads to a more elaborate way of connecting and grouping clauses into different units of discourse. In this way, they will also be able to demonstrate how texts can be built up through clauses, phases, and stages in a particular genre, without the need to be interpreted in conjunctions. HIGHLIGHTS: This article attempt to find a new way of classifying internal and external conjunctive relation that is comprised of conjunction, continuative and metaphor. Martin (2007) argues that only conjunction that perform external and inter. This article exhibits that actually external and internal roles can also be performed by continuative and metaphor. Some types of logical metaphors and continuations can not only operate externally to connect events and qualities, but can also function internally to organize evidence and arguments in a text.